Design and Development of a Multi-Blade Horizontal Axis Wind Turbine as an Alternative Energy Source in Talang Solok Regency - Faruqi, Fiqri Al; Modika , Yendri; Rabiula , Andre; Tessal , Dasrinal; Waladi , Akhiyar; Gusri , Lailal; Wijaya , Ali Satria; Wirasapta , Andicho Haryus; Triantini, Dewi (DPTE FT UNY, 2026)
Indonesian rural and highland areas have considerable potential for developing small-scale renewable energy, especially utilizing wind resources with low to moderate wind speeds. This research outlines the creation, design, and assessment of a six-blade horizontal axis wind turbine (HAWT) aimed at facilitating off-grid and decentralized electricity production in Talang, Solok Regency. To enhance the design methodology, a comparative design evaluation was performed by analyzing three-blade, four-blade, and six-blade rotor setups concerning starting torque traits, suitability for low wind speeds, and operational stability documented in earlier research. The six-blade design was chosen for its improved self-starting ability and dependable performance at wind speeds under 7 m/s. The created prototype features a rotor diameter of 1.5 m, a blade length of 0.75 m, a 1:5 gear ratio, and a 200 W DC generator. Performance testing took place over two months (August–September 2025) in natural wind conditions varying between 4.8 and 7.1 m/s. The turbine produced an open-circuit voltage of 2.5–4.4 V, and when under load, the peak electrical power output was 1.52 W. The determined power coefficient (Cp) varied from 0.12 to 0.18, demonstrating efficient energy conversion in low-speed wind conditions. The findings indicate that the suggested multi-blade HAWT design provides a technically viable, context-suitable, and scalable option for rural electrification, community-level renewable energy systems, and educational uses in areas with comparable wind conditions.